(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2021)
Architecture is one part of culture, which reflects the development of human life from time to time and displays various types of life (Sharr 2012). The embodiment of architectural studies can appear in various perspectives, such as the study of technology, symbols, open space, landscape, interior and also architectural education, as in the articles of ARTEKS in this edition volume 6 issue 2, August 2021.